Earnings and Employment in Foreign-Owned Firms - Dave C. Maré; Lynda Sanderson; Richard Fabling (Institute for the Study of Labor (IZA), 2014)
This paper examines remuneration and labour mobility patterns among workers in foreign-owned firms operating in New Zealand. By tracking workers as they move across jobs, we document the extent of the "foreign wage premium" distinguishing between compositional factors (eg, differences in industry and employment composition across foreign and domestic firms) and remaining differences in wage levels and growth rates. We find that much of the average earnings gap between foreign and domestically-owned firms is due to compositional factors foreign firms tend to be larger and employ workers who would have received relatively high wages regardless of where they worked. However, even among apparently similar workers and firms, we find a two to four percent earnings gap between workers in domestic and foreign-owned firms. This gap is primarily associated with a wage increase of around two percent on moving from a domestic to a foreign firm, augmented by higher wage growth among foreign-owned firms. These premia appear to be specific to foreign-firm employment, as workers who return to domestically-owned firms do not appear to retain the additional earnings in their subsequent jobs. We then consider whether foreign-owned firms source workers differently from other New Zealand firms and whether there are systematic differences in the destinations of departing employees by firm ownership. Although foreign-owned firms do not appear to preferentially hire recent immigrants, employees of foreign-owned firms are more geographically mobile within New Zealand and are more likely to emigrate within a year of leaving their job.
Keywords: D22; J31; F23; 330; foreign direct investment (FDI); earnings; labour mobility